Propuesta de un plan de gestión de cobranza para generar liquidez en la Edpyme Marcimex S.A. provincia de Trujillo. - Sebastian Pérez, María Del Pilar (2016)
This work was done in order to improve collections management in the Edpyme Marcimex S.A. through a proposal for management of accounts receivable so as to improve the generation of liquidity in the company; as there are clients which have been granted a credit, however, a percentage of these fail to timely payment of their dues, thus generating a collection problem. However, many problems with the collection could be avoided if will ensure that preliminary to proceedings are conducted properly, just as if they were monitors your debt where the customer perceives collection management as continuous and not sporadic, hence the timely and fast collection actions by the various participants in the management monitoring is very important. Thus to achieve the objectives techniques of data collection they were applied through a survey of staff collection company consisting of a sample of 52 people and interview the head of Credit Portfolio is made of the organization , just as documentary material was used as magazines, books, theses, accounting information of financial statements, guidelines and policies EDPYME MARCIMEX SA At the end of the investigation it was concluded that the personnel responsible for collection management lacks procedures to help them improve the contribution of this department, a situation that was solved with the strategic objectives comprising the proposed strategic plan.